The Effect of Using Artificial Intelligence on Fourth-Grade Science Students' Acquisition of Biology Concepts (Journal of the College of Basic Education, 2026)
This research aims to identify the impact of using artificial intelligence on the acquisition of biological concepts by fourth-grade science students in biology by verifying the validity of the following hypothesis: (There is no statistically significant difference at a significance level of (0.05) between the average scores of the students in the control group who study according to the traditional method in the biological concepts acquisition test) The experimental design was chosen with two experimental and control groups, one of which partially controls the other, from the same group after the post-test to acquire biological concepts. To verify the research hypothesis, a deliberate sample of (50) students was chosen and distributed into two experimental groups, the number of which was (25) students, and the control group, the number of which was (25) students .The equivalence was carried out between the students of the two research groups according to the following variables: (previous knowledge of biology, previous achievement in biology, intelligence) the academic year's first semester (2024–2025). The researcher chose five chapters from the Biology I textbook for the fourth scientific grade as the subject matter to be taught during the experimental period. .The behavioral objectives were formulated for the subjects that will be studied, and they were (151) behavioral objectives according to Bloom’s level (remembering, understanding, application, analysis, synthesis, evaluation). After completing the experiment, applying the test of acquiring biological concepts in biology and acquire the outcomes, the information was processed statistically using the t-Test for two independent samples, and the following findings were obtained: (In the biological concepts acquisition test, the experimental group that studied using artificial intelligence performed better than the control group that studied using the conventional method. Therefore, the researcher recommends some recommendations and suggestions.